Ethnomathematics and Spatial Geometry in Traditional Architecture and Artifacts of Kampung Kuta: An Ethnographic Study - Aripin; Anti Wijayanti; Nani Ratnaningsih (Research Collaboration Community (Rescollacom), 2026)
This study examines how three-dimensional geometric concepts are applied in the daily lives of the residents of Kampung Kuta, a traditional settlement in Karangpaningal Village, Tambaksari District, Ciamis Regency. The research employs an ethnographic approach to ethnomathematics to explore the relationship between local culture and mathematical knowledge. Data were collected through direct observation, in-depth interviews with residents, and the documentation of various related records. The findings reveal that various community activities, including the process of designing and constructing traditional houses and crafting tools, are rich in the application of spatial geometry principles. For instance, the distinctive roof shapes of stilt houses and the use of natural materials demonstrate a profound understanding of three-dimensional geometric concepts. This study reinforces the view that integrating local cultural elements into mathematics education can serve as an effective alternative for learning geometry in a more meaningful and contextualized manner.